2022
DOI: 10.48550/arxiv.2207.09434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Remarkably Luminous Galaxy Candidates at $z\approx10-12$ Revealed by JWST

Abstract: The first few hundred Myrs at z > 10 mark the last major uncharted epoch in the history of the Universe, where only a single galaxy (GNz11 at z ≈ 11) is currently spectroscopically confirmed. Here we present a search for luminous z > 10 galaxies with JWST /NIRCam photometry spanning ≈ 1 − 5µm and covering 49 arcmin 2 from the public JWST Early Release Science programs (CEERS and GLASS). Our most secure candidates are two M UV ≈ −21 systems: GLASS-z13 and GLASS-z11. These galaxies display abrupt 2.5 mag breaks … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 55 publications
8
77
0
Order By: Relevance
“…There are 39 galaxies in the final high-redshift (𝑧 > 8.5) sample uncovered by our analysis of the ERO/ERS JWST NIRCam imaging, with 16 found in SMACS0723, 21 in CEERS, and only 2 in GLASS. Both of the high-redshift galaxies we have found here in the GLASS field have been independently discovered by Naidu et al (2022) and Castellano et al (2022), namely GLASS-1698 and GLASS-17487 in our sample which we find to lie at 𝑧 = 10.56 and 𝑧 = 12.42 respectively (consistent with the independently reported photometric redshifts). We fail to recover robust high-redshift solutions for any of the five sources that Castellano et al (2022) reported in their fainter sample.…”
Section: The Final Jwst Galaxy Samplesupporting
confidence: 92%
“…There are 39 galaxies in the final high-redshift (𝑧 > 8.5) sample uncovered by our analysis of the ERO/ERS JWST NIRCam imaging, with 16 found in SMACS0723, 21 in CEERS, and only 2 in GLASS. Both of the high-redshift galaxies we have found here in the GLASS field have been independently discovered by Naidu et al (2022) and Castellano et al (2022), namely GLASS-1698 and GLASS-17487 in our sample which we find to lie at 𝑧 = 10.56 and 𝑧 = 12.42 respectively (consistent with the independently reported photometric redshifts). We fail to recover robust high-redshift solutions for any of the five sources that Castellano et al (2022) reported in their fainter sample.…”
Section: The Final Jwst Galaxy Samplesupporting
confidence: 92%
“…We measured 𝑛 = 1.1 ± 0.2 for SMACS_z16a, which corresponds to disk-like profile. Such a morphology was also observed for GLz13 (Naidu et al 2022), as well as in several other high-redshift candidates reported in Adams et al (2022). The existence of well settled disks at early epochs will provide strong constraints on theoretical models of galaxy formation.…”
Section: Discussionsupporting
confidence: 67%
“…While some of our sources are relatively bright, they all have luminosities around, or below, the characteristic luminosity 𝑀 ★ at 𝑧 ∼ 9 − 10 (Oesch et al 2018;Bouwens et al 2021). The highest redshift candidate in our sample, SMACS_z16, has an intrinsic UV magnitude of 𝑀 UV = −21.23 ± 0.27, which is fainter than previous the very high redshift candidates Gn_z11 and HD1, and slightly brighter than the recently discovered candidate GLz13 (Naidu et al 2022). Moreover, the yield of the galaxy hunt presented in this paper is surprisingly high, with the discovery of 2 candidates at 𝑧 ∼ 16, 2 candidates at 𝑧 ∼ 12, and 11 candidates at 𝑧 = 10 − 11.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations